Design of Wear-Resistant Diecast AlSi9Cu3(Fe) Alloys for High-Temperature Components - Giulio Timelli; Alberto Fabrizi; Simone Vezzù; Alessandro De Mori (Metals, 2019)
Type AlSi9Cu3(Fe) alloy has been modified by alloying with iron, manganese, and chromium elements to develop wear-resistant diecast hypoeutectic Al−Si−Cu alloys that can be applied for high-temperature applications. Several alloys have been produced by varying iron, manganese, and chromium levels (0.80, 1.00, 1.20 wt.% for Fe; 0.25, 0.40, 0.55 wt.% for Mn, and 0.06, 0.10 wt.% for Cr). Brinell hardness measurements and pin-on-disk wear tests have been conducted from room temperature up to 200 °C. The microstructural changes that occurred with the different alloying levels have been quantitatively examined by metallographic and image analysis techniques. The results showed how the increasing content of the Fe, Mn, and Cr promoted the precipitation of both primary and secondary Fe-enriched particles, mainly with polyhedral, blocky, and star-like morphologies. These compounds showed high hardness that is not affected by chemical composition and morphology variation. At high temperatures, the diecast alloys always showed lower average hardness and wear resistance, especially at 200 °C; however, a greater amount of Fe-rich particles can compensate the alloy softening.